2015
DOI: 10.1088/1742-6596/627/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nuclear vibration on the ionization process ofH2+in ultrashort intense laser field

Abstract: Abstract. By numerically solving the time-dependent Schrödinger equation, we calculate the ionization probability of a vibrating H + 2 exposed to ultrashort intense laser fields. The results show that the ionization probability increases by time and gets a saturation value. We also find that with some first vibration levels, the ionization probability from a higher vibration level is larger than that from a lower one. However, with higher vibration levels, at a certain level the ionization probability will tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…To interpret in-depth the dependence of even-to-odd ratio on the nuclear-charge ratio Z 1 /Z 2 , we consider the analytical expression of interference factors presented in Eqs. (10) and (11), causing odd and even harmonics [17]. Since the HHG signal is proportional to the transition dipole as described in Subsec.…”
Section: Iii1 Dependence Of Even-to-odd Ratio On Nuclear-charge Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…To interpret in-depth the dependence of even-to-odd ratio on the nuclear-charge ratio Z 1 /Z 2 , we consider the analytical expression of interference factors presented in Eqs. (10) and (11), causing odd and even harmonics [17]. Since the HHG signal is proportional to the transition dipole as described in Subsec.…”
Section: Iii1 Dependence Of Even-to-odd Ratio On Nuclear-charge Ratiomentioning
confidence: 99%
“…In the past, many studies have been focused on atoms [2,6,7], and then expanded to symmetric molecules [3,4,[8][9][10][11][12], whose HHG spectra contain only odd harmonics due to the timespatial symmetry of the laser-atom/molecule system [13,14]. Recently, much attention has been paid to asymmetric molecules such as HeH 2+ , CO, OCS, HCl [15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Using the similar 1D model in the non-Born-Oppenheimer (NBO) approach, Nguyen et al . 23 found that the ionization probability initially increases and subsequently decreases as the vibrational level of H 2 + increases.…”
mentioning
confidence: 99%